Manual emasculation and pollination techniques for tomato - Navya, Kagita; Rao, Deepak; Choudhary, Ravish; Yadav, Shiv Kumar; Yadav, Sangita (Indian Horticulture, 2024)
Tomato (Solanum lycopersicum L.) is a globally significant crop with a high economic value and optimizing pollination is crucial for enhancing fruit yield and quality. This article focuses on the methods of hand emasculation and pollination in tomato plant, aiming to provide insights into the practices that contribute to improved fruit set and overall crop productivity. Hand emasculation involves the removal of male reproductive organs (anthers) from tomato flowers to control and direct the pollination process. This technique is particularly relevant in hybrid seed production, where controlled pollination ensures the desired genetic traits. The timing and precision of emasculation are critical factors, as they influence the success of subsequent pollination efforts. Various pollination techniques are employed to transfer pollen from the male (anther) to the female (stigma) flower parts. Natural pollination by wind and insects is common in open-field cultivation, but controlled environments such as greenhouses often require manual intervention. Hand pollination, using brushes or vibrating tools, allows growers to exert precise control over the pollination process, leading to increased fruit set and uniformity. Understanding the floral biology of tomatoes, including flower structure, timing of anthesis and pollen viability, is essential for successful hand emasculation and pollination. Factors such as temperature, humidity and light conditions also influence the effectiveness of these techniques. Additionally, the choice of cultivar and the specific goals of cultivation, such as fruit size, shape and yield impact the selection of appropriate hand emasculation and pollination method.